Magnetic Properties of Steel Ball Samples, Investigated before and after Nitriding - H. Fuks; S.M. Kaczmarek; G. Leniec; J. Michalski; B. Kucharska; P. Wach (Archives of Metallurgy and Materials, 2018)
Group of steel balls with different chemical composition, diameters and nitriding treatment parameters were investigated with using magnetic resonance and magnetization methods. Emerging nitrided regions consists of diffusion and surface layer of iron nitrides. The thickness of the individual layers depends on the type of steel and process parameters. Resonance signal shape and position were successfully described in the ferromagnetic resonance regime expected for dense iron magnetic system. Influence of the sample size, thermal treatment and carbon content on the absorption signal has been analyzed. Significant magnetic anisotropy has been revealed, as well as non-usual increasing of the magnetization as a function of temperature. It suggests, that overall antiferromagnetic ordering, destroyed by thermal movement, lead to increasing of the ferromagnetic region.